Using AI in Telegram Bots for Earthquake Information Delivery and Analysis - Justicea, Ayu Adi; Agustin, Rala Kurniawan; Suko , Suko; Harahap, Darwin; Sinambela, Marzuki (Universitas Methodist Indonesia, 2025)
Indonesia is located in the Pacific Ring of Fire, making it vulnerable to earthquake activity. Earthquake events often require fast and accurate information delivery to reduce the impact of disasters. However, conventional systems often face obstacles such as information delays and lack of real-time impact analysis. Advances in artificial intelligence (AI) and machine learning (ML) provide opportunities to overcome these problems. AI is able to process seismic data efficiently, detect earthquake patterns, and predict their impact. By utilizing Telegram bots as a medium, earthquake information can be delivered quickly through real-time notifications, which are easily accessible to the public. The development of AI-based Telegram bots aims to provide earthquake information automatically, including location, magnitude, and potential impact, as well as analyze historical data to predict seismic activity trends. This solution is expected to increase public awareness and response in dealing with earthquake disasters.